The admixture of Quercus sp. in Pinus sylvestris stands influences wood anatomical trait responses to climatic variability and drought events - Giberti, Giulia Silvia; von Arx, Georg; Giovannelli, Alessio; du Toit, Ben; Unterholzner, Lucrezia; Bielak, Kamil; Carrer, Marco; Uhl, Enno; Bravo, Felipe; Tonon, Giustino; Wellstein, Camilla (Frontiers in Plant Science, 2023)
Introduction Forests are threatened by increasingly severe and more frequent drought events worldwide. Mono-specific forests, developed as a consequence of widespread management practices established early last century, seem particularly susceptible to global warming and drought compared with mixed-species forests. Although, in several contexts, mixed-species forests display higher species diversity, higher productivity, and higher resilience, previous studies highlighted contrasting findings, with not only many positive but also neutral or negative effects on tree performance that could be related to tree species diversity. Processes underlying this relationship need to be investigated. Wood anatomical traits are informative proxies of tree functioning, and they can potentially provide novel long-term insights in this regard. However, wood anatomical traits are critically understudied in such a context. Here, we assess the role of tree admixture on Pinus sylvestris L. xylem traits such as mean hydraulic diameter, cell wall thickness, and anatomical wood density, and we test the variability of these traits in response to climatic parameters such as temperature, precipitation, and drought event frequency and intensity. Methods Three monocultural plots of P. sylvestris and three mixed-stand plots of P. sylvestris and Quercus sp. were identified in Poland and Spain, representing Continental and Mediterranean climate types, respectively. In each plot, we analyzed xylem traits from three P. sylvestris trees, for a total of nine trees in monocultures and nine in mixed stands per study location. Results The results highlighted that anatomical wood density was one of the most sensitive traits to detect tree responses to climatic conditions and drought under different climate and forest types. Inter-specific facilitation mechanisms were detected in the admixture between P. sylvestris and Quercus sp., especially during the early growing season and during stressful events such as spring droughts, although they had negligible effects in the late growing season. Discussion Our findings suggest that the admixture between P. sylvestris and Quercus sp. increases the resilience of P. sylvestris to extreme droughts. In a global warming scenario, this admixture could represent a useful adaptive management option.